Birthday wishes - Bradford, Clare (Thomas Nelson Melbourne, 1994)
Birthday Wishes by Clare Bradford is a heartwarming children$1 (Bs book that explores the excitement and joy of celebrating a birthday. The story follows a young child who eagerly prepares for their special day, making a list of birthday wishes and dreaming of the perfect party. Along the way, the protagonist learns that the best gifts are not material things, but the love, friendship, and happy moments shared with family and friends. With charming illustrations and a gentle narrative, the book highlights the importance of gratitude and the simple pleasures that make birthdays truly magical.s